2019
DOI: 10.4274/imj.galenos.2019.37974
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipid Parameters in Patients Receiving Vitamin B12 Therapy

Abstract: Amaç: Yağ asit katabolizmasında rol alması ve serum lipitleri ile ilişkisinin gösterilmiş olması sebebiyle vitamin B12 takviyesinin serum lipit seviyelerini etkileyebileceğini düşünüyoruz. Bu çalışmada, vitamin B12 tedavisi alan hastalarda serum lipit ve glikoz değerlerinin etkilenip etkilenmediği araştırılmıştır. Yöntemler: Bu çalışma retrospektif gözlemsel bir araştırmadır. Bu çalışmada, aile hekimliği polikliniğine başvurmuş hastaların kayıtları geriye dönük incelenmiş, glikoz, lipit ve vitamin B12 gibi ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…Serum vitamin B12 level was found to be negatively correlated with TG and positively correlated with HDL (22,23). In our study, the mean B12 level was high, it was not associated with TG, and it showed a negative correlation with HDL.…”
Section: Discussionsupporting
confidence: 38%
“…Serum vitamin B12 level was found to be negatively correlated with TG and positively correlated with HDL (22,23). In our study, the mean B12 level was high, it was not associated with TG, and it showed a negative correlation with HDL.…”
Section: Discussionsupporting
confidence: 38%
“…Son zamanlarda yapılan çalışmalarda vitamin B12 yetersizliği olanlarda obezite sıklığının artığı belirtilmektedir (26,27,28). İlave olarak vitamin B12 ile HDL arasında pozitif, trigliserit ile negatif korelasyon olduğu (29) ve vitamin B12 alanlarda trigliserit seviyelerinin azaldığı ileri sürülmüştür (30). Yine sildenafil kullanan hastalarda görülen ağız ve göz kuruluğu yan etkilerinin vitamin B12 yetersizliğinde daha ağır ve uzun süreli olduğu iddia edilmektedir (31).…”
Section: Introductionunclassified
“…The dyslipidemia inhibitory mechanism of folic acid is mediated by its anti-inflammatory effect and inhibition of oxidative stress and lipid peroxidation [23,24]. Likewise, in a study done by Sezgin and Becel [24]. Vitamin B12 supplementation significantly reduced the total cholesterol and triglycerides level when compared between baseline and post-treatment.…”
Section: Talikotimentioning
confidence: 96%
“…The dyslipidemia inhibitory mechanism of folic acid is mediated by its anti-inflammatory effect and inhibition of oxidative stress and lipid peroxidation [23,24]. Likewise, in a study done by Sezgin and Becel [24].…”
Section: Talikotimentioning
confidence: 97%